Diagnostic impact of promoter methylation and E-cadherin gene and protein expression levels in laryngeal carcinoma - Starska, Katarzyna; Forma, Ewa; Lewy-Trenda, Iwona; Papież, Paweł; Woś, Jan; Bryś, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Inactivation of the tumor suppressor E-cadherin (CDH1) and its decreased expression is an important occurrence during carcinogenesis. Nevertheless, the relationship of CDH1 expression and the promoter methylation with laryngeal cancer cell aggressiveness is still unclear. The purpose of this study was to elucidate the gene and protein E-cadherin expression and the DNA methylation levels and to describe the correlations with morphological features in squamous cell laryngeal cancer. Material and method s: The authors studied E-cadherin and the DNA methylation level in 86 cases to gain a further understanding of the clinicopathologic significance of analyzed parameters. The pathological evaluation included pTNM classification and the tumor front grading (TFG) criteria. Quantitative analysis of the amplified product in real time (qRT-PCR) for estimation of CDH1 mRNA was used. The methylation status was investigated by using methyl-specific polymerase chain reaction (MSP). The level of CDH1 protein expression by Western blot was determined. Results : Downregulation of E-cadherin was found to be related to promoter methylation (p < 0.001). In tumors with the highest invasiveness according to TFG criteria the lowest E-cadherin gene and protein level in the study group was observed (p = 0.046 and p = 0.0002, respectively). In SCLC with muscle and cartilage invasion and disperse infiltration the lowest CDH1 gene and protein expression was noted (p = 0.0003 and p = 0.003 for deep invasion, p = 0.033 and p = 0.003 for multifocal infiltration, respectively). Conclusions : The current findings sug-gest an association of E-cadherin tumor expression with progression of laryngeal cancer. CDH1 gene level may be an auxiliary molecular marker for advanced cases of laryngeal carcinoma; however, further studies are necessary.